EFEKTIVITAS MEDIA E-LEARNING BERBASIS EDMODO TERHADAP MATA KULIAH BUNPOU I PADA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI JAKARTA - Mohamad, Sukesta; Astuti Retno Lestari , Dwi; Kusuma Hapsari , Eky (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2019)
This paper is a research report about the effectiveness of Edmodo-based e-learning media on Bunpou I courses in Japanese language education, Universitas Negeri Jakarta. The method used in this research was True Experimental by using the Pre-test Post-test Control Group Design model. The sample and population in this study were class A and class B in semester I of 2018 in the Japanese language study program, Jakarta State University. The instrument used in this study was a test in the form of a pretest - posttest, and a non test in the form of a questionnaire. Based on the results of data analysis, it can be scen that learning using Edmodo-based c-learning media on Bunpou I courses gets t-count of -0.621 which is smaller than t-table of 2.021 at a significance level of 0.05 (5%). with df 40. So t-count < t-table (0.621 <2.021). Thus there is no significant difference between Bunpou I learning using Edmodo based e-learning media and Android-based e-learning media. Then the experimental class produces n-gain of 0.67, which means the level of effectiveness is in the criteria of being. Whereas in the control class it produces n-gain of 0.69 which means that the level of effectiveness is also in the criteria of being. Then the value of effectiveness obtained from the results of the n-gain ratio of the experimental and control classes is 0.97 (0.97 <l). Thus it can be concluded that learning. using Edmodo-based e-learning media is no more effective than learning using Android-based e-leaming media on Bunpou l.